An improved model for fragment-based lead generation at AstraZeneca. Issue 8 (August 2016) - Fuller, Nathan; Spadola, Loredana; Cowen, Scott; Patel, Joe; Schönherr, Heike; Cao, Qing; McKenzie, Andrew; Edfeldt, Fredrik; Rabow, Al; Goodnow, Robert
Highlights: AZ fragment libraries designed for primary screening techniques, X-ray, NMR and SPR. Planar and 3D fragments are shown to be complementary in exploring binding pockets. 49% of all fragment hits at AZ from 2012 to 2015 have been 3D in nature (PBF >0.25). The proportion of 3D hits for PPI targets and all other target classes is the same. Abstract : Modest success rates in fragment-based lead generation (FBLG) projects at AstraZeneca (AZ) prompted operational changes to improve performance. In this review, we summarize these changes, emphasizing the construction and composition of the AZ fragment library, screening practices and working model. We describe the profiles of the screening method for specific fragment subsets and statistically assess our ability to follow up on fragment hits through near-neighbor selection. Performance analysis of our second-generation fragment library (FL2) in screening campaigns illustrates the complementary nature of flat and 3D fragments in exploring protein-binding pockets and highlights our ability to deliver fragment hits using multiple screening techniques for various target classes. The new model has had profound impact on the successful delivery of lead series to drug discovery projects. Abstract : This description of the fragment library and approach of AstraZeneca to fragment-based lead generation shows that 2D and 3D fragments provide complementary hits to explore binding pockets, and that both can deliver 3D lead series.